A prototype magnetically levitated stepping motor using high Tc bulk superconductors. - Komori, M.
A magnetically levitated stepping motor using high Tc superconductors has been newly developed. The levitated stepping motor consists of a cylindrical rotor with superconductors and a stator with eight electromagnets. The rotor measures 10 mm in diameter, 46 mm in length, and 18 g in mass. The superconductors of the rotor are field-cooled in liquid nitrogen. The levitated rotor is driven by an eight-phase excitation. The rotor spins as the excitation phases of the electromagnets shift one by one. The rotation angle by each step is 45°. The experimental result shows that the rotor speed is limited to about 400 rpm by axial displacements. During the rotation, the radial displacement of the rotor is less than 0.4 mm. Magnetic flux density in the superconductors is studied before and after continuous rotations. These show that there is a possibility that the levitated stepping motor will be realized
Keywords: Magnetic flux density; Magnetic levitation; Rotor; Stepping motor; High Tc superconductor